Pre-reading Activities: University ESL/EFL Teachers’ Practices and Views - Adhikari, Bal Ram; Shrestha, Kumar Narayan (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
The literature on reading pedagogy has recognized the pivotal role of pre-reading activities in preparing students as readers for the actual act of reading. In this regard, the current paper aimed to investigate University ESL/EFL teachers’ use of pre-reading activities in teaching B.Ed. English major reading courses at a constituent campus of Tribhuvan University. To this end, a case study design was adopted comprising classroom observation and semi-structured interview methods to collect data from four purposively selected English teachers. The findings show personalization of the topic, contextualization of the topic, digging into the title, pre-teaching key vocabulary items, and knowing the author as the most frequently used pre-reading activities. Despite this, students were found to be inadequately engaged in the pre-reading stage for want of variety in pre-reading activities and students’ poor participation. Moreover, coursebook pre-reading activities did not form part of reading lessons for several reasons. Finally, implications are considered for the integration of pre-reading activities for effective reading pedagogy.